Kajian Perempuan sebagai Pelaku KDRT Ditinjau dari Perspektif Victim Precipitation - Panjaitan, Gabrine Afni Tiolina; Nurhadiyanto, Lucky (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The phenomenon of Domestic Violence (KDRT) has always been the main concern of most people. This is because this action involves people who have good personal relationships with the victim. There are various types of domestic violence that are often published in the mass media, such as violence that occurs most often, such as violence against husbands against wives, parents against children and vice versa, uncles against their nephews, or employers against household assistants (ART). However, it is rare to find cases of domestic violence committed by women, especially violence committed by wives against husbands. This study aims to analyze and examine the reasons why a woman or wife can commit acts of violence against their partner through the theory of victim precipitation, courtesy of Marvin F. Wolfgang (1957) and Larry J. Siegel (2016). This study uses a qualitative research approach with a phenomenological research type in order to explore a phenomenon of domestic violence committed by wives against husbands. The results of this study indicate that there are various factors that stimulate wives to commit domestic violence against their husbands, namely: a) financial factors; b) an affair factor; c) a communication factor; and d) factor wife’s background. The existence of this research is to reveal that acts of domestic violence do not look at gender, so anyone can have the potential to become a perpetrator or victim of domestic violence.